2010
DOI: 10.1016/j.ijdevneu.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Guanidino compounds inhibit acetylcholinesterase and butyrylcholinesterase activities: Effect neuroprotector of vitamins E plus C

Abstract: Hyperargininemia is a metabolic disorder biochemically characterized by tissue accumulating of arginine and other guanidino compounds. Convulsions, lethargy and psychomotor delay or cognitive deterioration are predominant clinical features of this disease. Although neurologic symptoms predominate in this disorder, their pathophysiology is still unknown. In the present study we initially investigated the in vitro effect of arginine, homoarginine, N-acetylarginine and argininic acid on acetylcholinesterase and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 65 publications
5
15
0
Order By: Relevance
“…These elements probably protected AchE activities via their antioxidant properties. Our hypothesis is in agreement with the study of Delwing‐de Lima et al () that has shown that antioxidants, like vitamins C and E, are able to prevent acetylcholinesterase alteration.…”
Section: Discussionsupporting
confidence: 94%
“…These elements probably protected AchE activities via their antioxidant properties. Our hypothesis is in agreement with the study of Delwing‐de Lima et al () that has shown that antioxidants, like vitamins C and E, are able to prevent acetylcholinesterase alteration.…”
Section: Discussionsupporting
confidence: 94%
“…Recent evidence suggests that besides AChE, BuChE catalyses the hydrolysis of the neurotransmitter, acetylcholine, and serves as a coregulator of cholinergic transmission [48]. During our experimental study, AChE and BuChE decreased in GA 3 group, suggesting the production of oxidative stress as reported by us and by others [49]. The decrease of AChE enzyme activity might be due, according to Das and Mukherjee [50], directly to pollutant effects on the active part of enzyme or indirectly to the inhibition of enzyme synthesis.…”
Section: Discussionsupporting
confidence: 76%
“…Neuroprotective effects of VC were previously observed through an increase of ChE activity in organisms exposed to anti-AChE chemicals (Bano and Bhatt, 2010;Delwing-de Lima et al, 2010). Similarly, VC was protective against CPF induced oxidative stress in tilapia (Özkan et al, 2012).…”
Section: Discussionmentioning
confidence: 83%